Automatic Approach Tendencies toward High and Low Caloric Food in Restrained Eaters: Influence of Task-Relevance and Mood - Neimeijer, Renate A. M.; Roefs, Anne; Ostafin, Brian D.; de Jong, Peter J. (Frontiers in Psychology, 2017)
Objective. Although restrained eaters are motivated to control their weight by dieting, they are often unsuccessful in these attempts. Dual process models emphasize the importance of differentiating between controlled and automatic tendencies to approach food. This study investigated the hypothesis that heightened automatic approach tendencies in restrained eaters would be especially prominent in contexts where food is irrelevant for their current tasks. Additionally, we examined the influence of mood on the automatic tendency to approach food as a function of dietary restraint. Methods. An Affective Simon Task-manikin (AST) was administered to measure automatic approach tendencies where food is task-irrelevant, and a Stimulus Response Compatibility task (SRC) to measure automatic approach in contexts where food is task-relevant, in 92 female participants varying in dietary restraint. Prior to the task, sad, stressed, neutral, or positive mood was induced. Food intake was measured during a bogus taste task after the computer tasks. Results. Consistent with their diet goals, participants with a strong tendency to restrain their food intake showed a relatively weak approach bias towards food when food was task-relevant (SRC) and this effect was independent of mood. Restrained eaters showed a relatively strong approach bias towards food when food was task-irrelevant in the positive condition and a relatively weak approach in the sad mood. Conclusions. The weak approach bias in contexts where food is task-relevant may help high-restrained eaters to comply with their diet goal. However, the strong approach bias in contexts where food is task-irrelevant and when being in a positive mood may interfere with restrained eaters' goal of restricting food-intake.